2012
DOI: 10.1155/2012/215258
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Transformation of Tall Oil into Biocomponent of Diesel Fuel

Abstract: One of the conventional kraft pulp mills produce crude tall oil which is a mixture of free fatty acids, resin acids, sterols, terpenoid compounds, and many others. This study is devoted to the issue of direct transformation of crude tall oil in a mixture with straight-run atmospheric gas oil to liquid fuels using three different commercial hydrotreating catalysts. Diesel fuel production is an alternative to incineration of these materials. High catalytic activity was achieved for all tested catalysts in temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The fatty and resin acids combination of tall oil offers a good platform to use it as a chemical source upon upgrading. , Upgrading processes are mainly based on the removal of oxygenates from the bio-oils by hydrodeoxygenation (HDO), supplemented by decarboxylation and decarbonylation in the presence of hydrogen . Conventional hydrotreating catalysts such as cobalt- or nickel-doped Mo on alumina (Al 2 O 3 ) support in sulfide form are usually employed for HDO. , Zeolites have also been proposed for upgrading in the absence of hydrogen, but oxygenates are mostly converted to carbonaceous deposits and to a lesser extent to paraffin range hydrocarbons. , Most of the earlier reports on crude tall oil (CTO) are based on an upgrading by zeolites and mainly discuss the production of aromatics and the methods to reduce coking at high temperatures (>400 °C). ,, More recently, Mikulec et al investigated the hydrotreating of CTO with atmospheric gas oil (AGO) and reported that NiMo and NiW hydrotreating catalysts can be used for the production of a biocomponent for diesel fuel . Tall oil fractions have also been studied, and several reports are available in literature describing the behavior of tall oil fractions, especially the fatty acid fraction, under hydrotreating conditions. ,, Different reaction mechanisms have been proposed for the formation of n -alkanes, water, CO 2 , CO, and propane from fatty acids. The behavior of the resin acid fraction is complex under these conditions and the mechanism for its ring rupture is less understood.…”
Section: Introductionmentioning
confidence: 99%
“…The fatty and resin acids combination of tall oil offers a good platform to use it as a chemical source upon upgrading. , Upgrading processes are mainly based on the removal of oxygenates from the bio-oils by hydrodeoxygenation (HDO), supplemented by decarboxylation and decarbonylation in the presence of hydrogen . Conventional hydrotreating catalysts such as cobalt- or nickel-doped Mo on alumina (Al 2 O 3 ) support in sulfide form are usually employed for HDO. , Zeolites have also been proposed for upgrading in the absence of hydrogen, but oxygenates are mostly converted to carbonaceous deposits and to a lesser extent to paraffin range hydrocarbons. , Most of the earlier reports on crude tall oil (CTO) are based on an upgrading by zeolites and mainly discuss the production of aromatics and the methods to reduce coking at high temperatures (>400 °C). ,, More recently, Mikulec et al investigated the hydrotreating of CTO with atmospheric gas oil (AGO) and reported that NiMo and NiW hydrotreating catalysts can be used for the production of a biocomponent for diesel fuel . Tall oil fractions have also been studied, and several reports are available in literature describing the behavior of tall oil fractions, especially the fatty acid fraction, under hydrotreating conditions. ,, Different reaction mechanisms have been proposed for the formation of n -alkanes, water, CO 2 , CO, and propane from fatty acids. The behavior of the resin acid fraction is complex under these conditions and the mechanism for its ring rupture is less understood.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the methods include high temperature esterification of tall oil fatty acids with methanol (White et al 2011) and use of HCl-methanol (Demirbas 2008). In other studies, Kocik et al (2017) screened solid catalysts for esterification of tall oil fatty acids with methanol, whilst Mikulec et al (2012) processed diesel oil components from tall oil using atmospheric gas oil on zeolite catalysts.…”
Section: Competition For Raw Materials With Increased Bioenergy Demandmentioning
confidence: 99%
“…Alkyd resins account for the largest demand among all intermediates manufactured from TOFAs, whereas soaps, detergents, and coatings hold the largest market share of TOFAs in terms of volume. More recently, TOFAs have been investigated for the production of biofuels including drop-in hydrocarbon fuels [11] and biodiesel [12,13] The market for TOFAs is expected to reach USD 1 billion in 2022 [14]. In the U.S., CTO has a floor price the equivalent of the value of natural gas as CTO can be used as a substitute to fossil fuels as a pulp mill lime kiln process fuel.…”
Section: Introductionmentioning
confidence: 99%